Effects of Long-Term Fertilization on Phosphorus Form and Availability in Black Soil - Enjia Lu; Cuilan Li; Yidan Geng; Tianfeng Liang; Jinjing Zhang (Applied Sciences)
This study explored the effect of the combined application of chemical and organic fertilizers on phosphorus morphology and its conversion to an active state. A long-term field positioning experiment comprising five treatments was conducted in black soil. The results concluded that the soil total phosphorus (TP), available phosphorus (AP), inorganic phosphorus, and organic phosphorus contents of all treatments ranked as follows: 1.5M1NPK > M2NPK > M1NPK > NPK > CK. The long-term application of chemical and organic fertilizers increased the proportion of soil reactive phosphorus and moderately reactive phosphorus but decreased the proportion of mildly active phosphorus and residual phosphorus. A phosphorus-31 nuclear magnetic resonance (31P NMR) spectral analysis showed that the contents of orthophosphate, pyrophosphate, phosphoric acid diesters, and orthophosphate acid monoesters increased with the application of chemical and organic fertilizers, of which 1.5M1NPK usually resulted in the highest increases. In conclusion, the long-term application of chemical fertilizers could promote the conversion of soil phosphorus into active phosphorus and improve the effectiveness of soil phosphorus, and the long-term use of organic and chemical fertilizers was more effective than the use of chemical fertilizers only, with 1.5M1NPK providing the best effects.